Primary non-refluxive megaureter in children: single-center experience and follow-up of 212 patients - Rubenwolf, Peter; Stein, Raimund (International urology and nephrology, 2016)
PurposePrimary non-refluxing megaureter (pMU) is a multifaceted and challenging congenital pathology of the urinary tract. We report our 23-year experience with this anomaly in terms of presentation, diagnostic work-up and management.Materials and methodsWe retrospectively reviewed the medical records of 212 children diagnosed with pMU between 1986 and 2009 at our institution. Mean follow-up was 45.17 (0-192) months.ResultsOf the total, 168 (79 %) children presented with upper urinary tract dilation on perinatal ultrasound screening. In 44 (21 %) patients, the diagnosis was made following diagnostic work-up of a urinary tract infection (UTI, 18 %) or flank pain (3 %). In total, 203 of 254 pMUs (79.9 %) were successfully treated conservatively during the 23-year observation period. Forty-eight children (23 %) underwent ureteric reimplantation. UTIs occurred in 91 of 212 children (43 %). Of these, 41 (45 %) occurred despite antibacterial infection prophylaxis. Within the past three decades, there has been a marked shift from surgical toward conservative therapy at our institution.ConclusionNeonatal renal ultrasound is the method of choice to timely identify children with pMU and, alongside dynamic renography, to monitor the clinical course. Nowadays, only a minor subset of children with asymptomatic course requires surgical correction. Antibacterial prophylaxis has the potential to reduce the risk of febrile UTIs. Prospective randomized studies are warranted to provide evidence of the beneficial effect of antibacterial prophylaxis.
Gesehen am 20.11.2019